A FoodSafeR perspective on emerging food safety hazards and associated risks - Leslie, John F.; Ezekiel, Chibundu N.; Wagner, Martin; Elliott, Chris; McNerney, Oonagh; Uyttendaele, Mieke; Yongning, Wu; Wang, Songxue; Okoth, Sheila; Lindsay, James; Rawn, Dorothea F. K.; Chan, Sheot Harn; et al. (Frontiers in Sustainable Food Systems, 2025)
The recently launched FoodSafeR initiative is a cooperative and coordinated approach to the identification, assessment, and management of emerging food security challenges and associated risks—both chemical and microbial. The FoodSafeR consortium includes global stakeholders across governmental, inter-governmental, academic and industrial institutions involved in food safety, research, and production. Consortium members have led in-depth discussions on identifying, assessing and managing chemical and microbial food safety issues resulting from climate change, emerging microbial and chemical contaminants, and evolving dietary preferences. Food safety research often is episodic in nature, increasing after a crisis and then decreasing when there are no major problems. Timely communications about and a central source containing data on previous outbreaks were identified as crucial issues to reduce the harm that could result from a food safety issue. In the course of the discussions, both new and old microbial and chemical hazards were identified for inclusion in a central database. The database could be used to develop artificial intelligence (AI) models to explain existing and predict emerging food safety risks. The FoodSafeR hub continuously collects and merges government, academic and private sector data to enable all stakeholders to better understand emerging risks, both chemical and microbial, and where they are found. As the database expands, climate change impacts on food safety can be documented and then integrated with public health data to rigorously assess the contributions of food safety to public health risks. The overall goal is to enhance global data sharing, improve food safety standards, and ensure the production of safe, accessible food for all populations thereby reducing the economic burden of foodborne illnesses, enhancing food security, and promoting sustainable food systems. The goal of this paper is to alert the global food safety community of the availability of this new resource and to provide information on the types of data it contains while encouraging others to contribute data that would broaden the information available and enable more timely and accurate identification of potential food safety issues throughout the world.